PENDAMPINGAN MANAJEMEN SEKOLAH BERMUTU DI MASA PANDEMI COVID-19 - Elperida J. Sinurat; Anton A. P. Sinaga; Henri Saragih; Jeudi A. T. P. Sianturi; Hotlan Butarbutar; Junika Napitupulu; Kristanty Marina N. Nadapdap; Mislan Sihite; Mangasa Panjaitan; Tiur Rajagukguk; Toman Panggabean; Selamat Siregar (Universitas Methodist Indonesia, 2021)
Community service aims to provide guidance to teachers in carrying out the tasks of the teaching and learning process. In this case, the method used is the lecture, discussion, and question and answer method. Through this, many inputs were obtained, including the characteristics of quality schools and of course quality human resources are needed, especially with the Covid 19 pandemic that has hit the city of Medan and the world in general. Quality school management starts from the principal, teachers, investment in finance and adequate infrastructure.